2020
DOI: 10.1039/c9ta11704k
|View full text |Cite
|
Sign up to set email alerts
|

Facile surface modification of LSCF/GDC cathodes by epitaxial deposition of Sm0.5Sr0.5CoO3via ultrasonic spray infiltration

Abstract: Ultrasonic spray infiltration is demonstrated by surface tailoring of LSCF/GDC cathodes by generating high dispersion and epitaxial deposition of Sm0.5Sr0.5CoO3 catalyst nanolayer, which promotes high and stable performance outcomes of the SOFCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…The performance tests demonstrated that Ag infiltration significantly improved the electrochemical performance and a maximum of 537 mWcm −2 power density was attained at 700°C. Song et al [152] infiltrated the Sm 0.5 Sr 0.5 CoO 3-δ (SSC) nano-particles into porous LSCF-GDC cathode. This doubled the cell performance and was attributed to the high mixed ionic and electronic conductivity of SSC.…”
Section: Single-cell Performancementioning
confidence: 99%
“…The performance tests demonstrated that Ag infiltration significantly improved the electrochemical performance and a maximum of 537 mWcm −2 power density was attained at 700°C. Song et al [152] infiltrated the Sm 0.5 Sr 0.5 CoO 3-δ (SSC) nano-particles into porous LSCF-GDC cathode. This doubled the cell performance and was attributed to the high mixed ionic and electronic conductivity of SSC.…”
Section: Single-cell Performancementioning
confidence: 99%
“…At temperatures below 800°C, LSM cathode was found to have high polarization losses due to its very low ionic conductivity 13 . Furthermore, at this temperature, LSM poorly performs because of the high activation energy ( E a ) of the ORR, resulting in an increase in electrode polarization resistance ( R p ) as the operation temperature decreases 14 …”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of cathodic oxygen reduction reaction (ORR) decreases significantly as the temperature decreasing, which is a key factor limiting the advancement for intermediate-temperature solid oxide fuel cell (IT-SOFCs) [1,2]. For this reason, finding more suitable cathode electrocatalysts with superior electrocatalytic activity is essential.…”
Section: Introductionmentioning
confidence: 99%